THE COMPARISON OF LEGAL DAMAGES FOR COPYRIGHT & BRAND INFRINGEMENT AMONG INDONESIA-CHINA LAWS - Heri Gunawan; Joni Emirzon; Muhammad Syaifuddin (UNISSULA, 2021)
Intellectual Property Rights or what is often abbreviated as HAKI is a legal protection given by a certain country to a person or group of individuals who express their ideas in the form of works. This law is a state territory. This means that a work will only be protected by rights in the country where the work originated to obtain IPR. As stated in the Copyright Laws, Intellectual Property Rights are exclusive rights granted by a regulation to a person or group of people for their copyrighted works. This protected work is in the form of intangible objects such as copyrights, patents, and trademarks and tangible objects in the form of information, technology, literature, art, skills, science, and so on. The idea of compensation law for copyright and trademark infringement in Indonesia, of course, can imitate the copyright law and trademark law of the People's Republic of China in regulating more clearly the calculation of the value of losses for copyright and trademark infringement in order to be able to provide legal certainty for the owner / rights holders whose rights have been violated. The research use normative juridical approach. The purpose of writing is to analyze and explain the calculation of compensation by looking at the criteria, evidence, basis, form and formulation of calculating compensation for copyright and trademark infringement. The results of the study stated that the law for compensation that arises as a result of copyright and trademark infringement according to positive law in Indonesia still does not regulate in detail the calculation of the value of the loss of both copyrights and trademarks. Copyright Act No.28 of 2014 and Trademark Act No.20 of 2016 only gives rights to the right owner/right holder to file a claim for compensation, but the law does not regulate how to determine the value of the loss for a copyright infringement as well as brands.